Effects of fat grip training on muscular strength and driving performance in division I male golfers - Cummings, P. M.; Waldman, H. S.; Krings, B. M.; Smith, J. W.; McAllister, M. J. (The Journal of Strength and Conditioning Research, 2018)
Fat grip (FG) training is implemented into strength and conditioning programs with the overall goal of increasing grip strength. Previous research assessing the effect of training with increased grip diameters compared with standard Olympic bar diameters has mainly been in acute settings. Therefore, the purpose of this study was to examine to effects FG training compared with normal diameter grip (CON) training during an 8-week periodized resistance training (RT) program in division I male golfers. Subjects (n = 10) were randomly assigned into 2 groups: the FG group (n = 5, scoring average: 75.4 ± 2.0) and CON group (n = 5, scoring average: 75.0 ± 0.5). Both groups participated in 8 weeks of RT (3 d/wk). The FG group completed every lift and repetition using FG, compared with the CON training group which used normal diameter bars. Pretraining and posttraining performance variables included swing speed, ball speed, driving distance, driving carry, maximum pull-ups to failure, right and left hand grip strength, and 1 repetition max trap-bar deadlift. The FG group demonstrated significant increases (p = 0.05) in ball speed, carry, drive distance, and left hand grip strength after 8 weeks of RT. In a population, such as low-handicap division I male golfers, FG training may allow for athletes to increase golf-specific performance after 8 weeks of periodized RT. Strength and conditioning coaches may use FG training over the course of a training program with athletes who require adequate grip strength to further elicit training adaptations.